THE RELATIONSHIP KNOWLEDGE ABOUT DENTAL CARIES IN CHILDREN AND GENESIS PRE SCHOOL IN TK PLUPUH II DESA BORANGAN KECAMATAN PLUPUH KABUPATEN SRAGEN - Andi Yulianto; Ahmad Syamsul Bahri (Universitas Sahid Surakarta, 2013)
Background: The results of a preliminary study of dental health status data obtained in September 2012 from the Puskesmas Plupuh II in TK Plupuh II Desa Borangan Kecamatan Plupuh Kabupaten Sragen by the number of students there are 44 children 30 children (75%) had dental caries, while existing health facilities Puskesmas Plupuh II have a dentist or dental nurse so that the absence of health can lead to maternal knowledge about dental care is also less and plus the low level of maternal education in the countryside. Objective: To know the relationship of maternal knowledge about the incidence of dental caries in pre-school children in kindergarten Plupuh II sub Desa Borangan Kecamatan Plupuh Kabupaten Sragen. Method: This research is analytic descriptives with cross sectional. Population and samples in this study were all mothers and pre-school children in kindergarten Plupuh II Desa Borangan Kecamatan Plupuh Kabupaten Sragen as many as 44 children. Data analysis techniques used by the analysis of Chi-Square (X2) Result: (1) Most of the respondents have less knowledge of as many as 23 people (52,3%), (2) Most of the children had dental caries status of as many as 39 children (88,6%), (3) There is a relationship between knowledge mothers with dental caries experience in preschool children in kindergarten Plupuh II Desa Borangan Kecamatan Plupuh Kabupaten Sragen (x2hit = 7,597 > x2tab = 5,991; p = 0,022 < 0,05). Conclusion: There is a relationship between maternal knowledge about the incidence of dental caries in pre-school children in kindergarten Plupuh II sub Desa Borangan Kecamatan Plupuh Kabupaten Sragen.